Individualised avatars with complete anatomy constructed from the ANSUR II 3-D anthropometric database. (2016) - Zientara, Gary P.; Hoyt, Reed W.
Individualised 3-D finite element (FE) mesh static avatars with complete labelled internal anatomy were constructed in a fully computerised fashion using 3-D body surface scan mesh data from the ANSUR II 3-D anthropometric database. A combination of skeleton matching, landmark matching and surface matching were employed in a fully automatic method to generate affine geometric transformations deforming a segmented 3-D FE mesh (i.e., having labelled tetrahedral elements) representing standard genderspecific human anatomy. The standard anatomy was deformed to fit into the FE mesh of an individual's body surface scan acquired in the ANSUR II anthropometric study. Two hundred fifty male avatars were computed.